Lactarius vividus sp. nov. (Russulaceae, Russulales), a widely distributed edible mushroom in central and southern China - Wang, Xianghua; Nuytinck, Jorinde; Verbeken, Annemieke (Phytotaxa, 2015)
Lactarius sect. Deliciosi includes a group of edible mushrooms with a worldwide geographical distribution. Although several species are considered choice edible mushrooms, taxonomic knowledge on this group in Asia is still fragmentary. A new species in L. sect. Deliciosi with orange latex, L. vividus, is described as an important wild edible mushroom that is widely distributed in central and southern China. Morphological analyses demonstrate that L. vividus encompasses high infraspecific morphological variation, which makes it difficult to clearly delimit its taxonomic boundary. Compared with other species having orange latex in L. sect. Deliciosi, L. vividus can be recognized by the vividly colored, subdistant to distant lamellae and heavy basidiospore ornamentation. It has been found to grow with four species of Pinus subg. Pinus including P. latteri, P. massoniana, P. taiwanensis and P. thunbergii. Phylogenetic analyses of the ITS region and glyceraldehyde-3-phophate dehydrogenase gene (gpd) support species delimitation and suggest ITS and gpd are good DNA markers to identify this new species.